2017
DOI: 10.1038/s41598-017-10667-6
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the electron dynamics of the excited state via higher-order spectral minimum

Abstract: A pump-probe scheme for monitoring the electron dynamics of the excited state has been investigated by numerically solving the two-state time-dependent Schrödinger equation based on the non-Born-Oppenheimer approximation. By adjusting the delay time between a mid-infrared probe pulse and an ultra violet pump pulse, an obvious minimum can be seen in the higher-order harmonic region. With electron probability density distribution, ionization rate and classical simulation, the minimum can be ascribed to the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The TDSE for a hydrogen atom interacting with orthogonally polarized laser fields is expressed in two-dimensional (2D) cartesian coordinates. The 2D-model has been used in many theoretical studies (see for instance 13,47 ) and has been shown to reproduce well the full three-dimensional calculations (see the Supplemental Material for details about the calculations 44 ), allowing thus a correct description of the dynamics involved in the hydrogen atom with less computational efforts. On the basis of this model, the TDSE is written as…”
Section: Methodsmentioning
confidence: 99%
“…The TDSE for a hydrogen atom interacting with orthogonally polarized laser fields is expressed in two-dimensional (2D) cartesian coordinates. The 2D-model has been used in many theoretical studies (see for instance 13,47 ) and has been shown to reproduce well the full three-dimensional calculations (see the Supplemental Material for details about the calculations 44 ), allowing thus a correct description of the dynamics involved in the hydrogen atom with less computational efforts. On the basis of this model, the TDSE is written as…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the harmonic generation also records the excited-state dynamics. [15,16] For the symmetric molecular ions, it can be encoded in both the lower-order [15] and the higher-order harmonics. [16] The former is attributed to the two-center interference, while the latter is ascribed to the electron localization.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] For the symmetric molecular ions, it can be encoded in both the lower-order [15] and the higher-order harmonics. [16] The former is attributed to the two-center interference, while the latter is ascribed to the electron localization. With dynamical symmetry breaking, the even harmonics from the symmetric molecular ions can manifest the excited-state dynamics in both linearly and elliptically polarized laser fields.…”
Section: Introductionmentioning
confidence: 99%
“…High-order harmonic generation (HHG) which is a useful tool to monitor quantum dynamics has been intensively investigated. [1][2][3][4][5][6][7] HHG could be used to produce attosecond pulse [8][9][10][11][12] that is a powerful tool to probe, track, control the dynamics of electron in ultrafast process. [13][14][15][16] Recently, linearly polarized attosecond pulse could be obtained from linear polarized harmonics in experiments, [17,18] and the HHG process is well described by semiclassical three-step model.…”
Section: Introductionmentioning
confidence: 99%